Characterization of slag from combustion of pulverized lignite with high calcium content in utility boiler - P. Pintana (2018)
The Mae Moh mine in northern Thailand, with its abundant lignite, is the primary energy source for the Mae Moh power plant, which uses pulverized coal combustion in superheated boilers to generate electricity for domestic consumption. The lignite reserves remaining in the mine may contain up to 40% CaO. Given this high calcium content, more frequent and severe slagging problems are likely to occur. To better understand the potential slag problem, this research investigates the characteristics and properties of the slag by collecting and analyzing different samples of boiler slag from the Mae Moh power plant. Employing scanning electron microscopy, energy dispersive X-ray spectroscopy, X-ray fluorescence, and X-ray diffraction, the surface morphologies of the different slag samples were found to be similar. The majority of the crystal surfaces were agglomerates of particle-like clay and irregular granules stacked together. The most abundant elements in the slag were oxygen, aluminum, silica and calcium. The major chemical components included CaO, SiO 2 , Al 2 O 3 , Fe 2 O 3 , and MgO. The minerals found in the slag were anorthite, gehlenite, akermanite, diopside, and esseneite. An increasing base-to-acid ratio reduced ash flow temperature. The Mae Moh lignite showed a medium to high slagging tendency. Increasing the slagging index led to a decrease in the ash fusibility temperature, due mainly to increasing amounts of Fe 2 O 3 and CaO. From this study, the high CaO and Fe 2 O 3 in the Mae Moh lignite clearly resulted in increased intensity of slag.